The blink reflex and its modulation – Part 1: Physiological mechanisms - Kofler, Markus; Hallett, Mark; Iannetti, Gian Domenico; Versace, Viviana; Ellrich, Jens; Téllez, Maria J.; Valls-Solé, Josep (Clinical Neurophysiology, 2024)
The blink reflex (BR) is a protective eye-closure reflex mediated by brainstem circuits. The BR is usually evoked by electrical supraorbital nerve stimulation but can be elicited by a variety of sensory modalities. It has a long history in clinical neurophysiology practice. Less is known, however, about the many ways to modulate the BR. Various neurophysiological techniques can be applied to examine different aspects of afferent and efferent BR modulation. In this line, classical conditioning, prepulse and paired-pulse stimulation, and BR elicitation by self-stimulation may serve to investigate various aspects of brainstem connectivity. The BR may be used as a tool to quantify top-down modulation based on implicit assessment of the value of blinking in a given situation, e.g., depending on changes in stimulus location and probability of occurrence. Understanding the role of non-nociceptive and nociceptive fibers in eliciting a BR is important to get insight into the underlying neural circuitry. Finally, the use of BRs and other brainstem reflexes under general anesthesia may help to advance our knowledge of the brainstem in areas not amenable in awake intact humans. This review summarizes talks held by the Brainstem Special Interest Group of the International Federation of Clinical Neurophysiology at the International Congress of Clinical Neurophysiology 2022 in Geneva, Switzerland, and provides a state-of-the-art overview of the physiology of BR modulation. Understanding the principles of BR modulation is fundamental for a valid and thoughtful clinical application (reviewed in part 2) (Gunduz et al., submitted).
CRIS-Team Scopus Importer:2024-04-12
Keywords: Anesthesia; Classical conditioning; Pain; Peripersonal space; Prepulse inhibition; Protective reflex